Recombinant expression and characterization of Canine circovirus capsid protein for diagnosis - Dankaona, Wichan; Nooroong, Pornpiroon; Poolsawat, Napassorn; Piewbang, Chutchai; Techangamsuwan, Somporn; Anuracpreeda, Panat (Frontiers in Veterinary Science, 2024)
Canine circovirus (CanineCV) is a contagious virus that causes severe gastroenteritis, diarrhea, respiratory disease, and vasculitis, often resulting in fatality among infected dogs. In this study, a recombinant Capsid protein (rCap) of CanineCV was expressed in the Escherichia coli (E. coli) Rosetta (DE3) pLysS host cell, followed by affinity purification, and then analyzed by SDS-PAGE, revealing a molecular weight of approximately 31 kDa. The antigenicity of the CanineCV rCap protein was confirmed through recognition by a rabbit anti-CanineCV rCap protein polyclonal antibody (PoAb). Additionally, the reactivity and specificity of this PoAb were assessed using indirect enzyme-linked immunosorbent assay (ELISA) and Western blot analysis before applying in an immunohistochemistry (IHC), namely, immunoperoxidase detection. The immunoperoxidase assay using rabbit anti-CanineCV rCap protein PoAb demonstrated that the CanineCV Cap protein was predominantly located in immune cells, especially lymphocytes and macrophages, within the spleen, lung, tracheobronchial lymph nodes, small intestine, and kidney. Similarly, the Cap protein was also found in pneumocytes in the lung and renal tubular epithelial cells in the kidney. These findings reflected the biological activity and cell tropism of the virus. Therefore, the recombinant Cap protein and its PoAb could be used for the development of a valuable diagnostic tool for CanineCV detection.